Application of biosensors in food quality control - Shams, Rafeeya; Singh, Jagmohan; Ashraf, Shafia; Manzoor, Mehnaza; Dar, Aamir Hussain (Journal of Postharvest Technology, 2020)
Food producers gradually demand for effective quality control procedures to satisfy and regulate the requirements of consumer to enhance the  production feasibility, automation, quality sorting and decreases time and cost of production. Also, there is the requirement for rapid and efficient  techniques to identify the allergens and pathogens present in the food product which can be fulfilled by the biosensors. Biosensors have the ability to  overcome all these disadvantages by offering quick, inexpensive as well as non-destructive procedures for quality control and pave way for the quick  identification of allergens, pathogens, and pesticide residues present in food. In this review, the basic principle behind biosensors and the generations  of biosensors have been highlighted. Various biosensor on the basis of technique used such as optical biosensor, potentiometric biosensor,  amperometric biosensor, thermometric biosensor, electrochemical biosensor, piezoelectric biosensor, impedance biosensor, fluorescence label biosensors have been emphasized. In this peculiar review, the various applications of biosensors in food safety, process monitoring, as well as  assessment of quality, including the detection of contaminants, pathogenic microorganisms, determination of antioxidants, heavy metals, quality  evaluation of various fruits and vegetables have been discussed in detail.
Keywords: Nanosensor; transducer; food industry; food safety; quality control